Great White Shark - Spilsbury, Richard (Chicago Heinemann Library, 2004)
What makes a great white shark warm-bodied, but not warm-blooded? How many teeth does a great white shark have? What are denticles?
1 - 6
Keywords: Great White Shark; Animals Under Threat